Low tendon stiffness and abnormal ultrastructure distinguish classic Ehlers‐Danlos syndrome from benign joint hypermobility syndrome in patients. Issue 11 (13th August 2014) - Nielsen, Rie Harboe; Couppé, Christian; Jensen, Jacob Kildevang; Olsen, Morten Raun; Heinemeier, Katja Maria; Malfait, Fransiska; De Paepe, Sofie SymoensAnne; Schjerling, Peter; Magnusson, Stig Peter; Remvig, Lars; Kjaer, Michael
Abstract : There is a clinical overlap between classic Ehlers‐Danlos syndrome (cEDS) and benign joint hypermobility syndrome (BJHS), with hypermobility as the main symptom. The purpose of this study was to investigate the role of type V collagen mutations and tendon pathology in these 2 syndromes. In patients (cEDS, n =7; BJHS, n =8) and controls (Ctrl, n =8), we measured patellar tendon ultrastructure (transmission electron microscopy), dimensions (magnetic resonance imaging), and biomechanical properties (force and ultrasonographic measurements during a ramped isometric knee extension). Mutation analyses ( COL5A1 and COL5A2 ) were performed in the patients. COL5A1 mutations were found in 3 of 4 of the patients with cEDS. Patellar tendon dimensions were similar between the groups, but large, irregular collagen fibrils were in 4 of 5 patients with cEDS. In the cEDS group, tendon stiffness and Young's modulus were reduced to 50% of that in BJHS and Ctrl groups ( P <0.05). The nonhypermobile, healthy controls were matched with the patients in age, sex, body weight, and physical activity, to compare outcomes. COL5A1 mutations led to structural tendon pathology and low tendon stiffness in cEDS, explaining the patients' hypermobility, whereas no tendon pathology was found that explained the hypermobility in BJHS.—Nielsen, R. H., Couppé, C., Jensen, J. K., Olsen, M. R., Heinemeier, K. M., Malfait, F., Symoens, S., De Paepe, A., Schjerling, P., Magnusson, S. P., Remvig, L., Kjaer, M., Low tendon stiffness and abnormal ultrastructure distinguish classic Ehlers‐Danlos syndrome from benign joint hypermobility syndrome in patients. FASEB J. 28, 4668–4676 (2014). www.fasebj.org